Analysis of Teacher Service Quality on Student Satisfaction at SMA Deli Murni Bandar Baru - Yohanes Kefi; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The data analysis technique used was simple linear regression analysis, t test and determination test. The results of the study concluded that the variable of teacher service quality affects student satisfaction. This can be seen from the ahsil t-test through the value of t-count > t-table, which is 6.777 > 1.656 and p value 0.000 < 0.05 , as well as the value of t-count